무인항공기 대응체계 도입 방안 - 박제홍; Jehong Park (한국항행학회논문지, 2017)
쉽게 조종이 가능한 소형 무인기가 빠르게 보급되고, 무인기 산업이 빠른 속도로 성장함에 따라 공중 보안(airspace security)에 취약한 보안/전략 시설의 보안성 확보에 무인기가 새로운 위협이 되고 있다. 이러한 위협이 다양해지면서, 위협에 대응하는 무인기 대응체계 개발에 대한 연구/개발도 빠르게 연구되고 있다. 본 논문에서는 소형 무인기 보급에 따른 여러 가지 위협 및 사고 사례를 기술하고, 무인기 개발 및 운용방식에 따라 맞춤형으로 개발되고 있는 무인기 대응체계 개발 동향을 무인기 대응체계의 개념, 탐지/식별방안 및 제압/대응방안으로 나누어 기술한 후, 드론을 포함한 소형 무인기 대중화에 따른 부작용을 최소화할 수 있는 기술적, 제도적 대안을 제안하고자 한다. As a popularization of small UAS to have improved flight performance and easiness of controlling, the UAS industry is increased and also small UAS is to be a new threat for airspace security of national strategic infrastructure. Rising the new threat makes the negative side effect of small UAS operation. This phenomena brought to new R&D needs “defense system” for small UAS/UAV - called Anti-Drone. The paper addressed case study of defects, accidents and threats by small UAS/UAV as world wide level, and research and development trend of UAS defense system as each technical category - CONOP (Concept of Operation), identification/recognition method and control/supremacy techniques. As a result, this suggests the direction what and where drone defense system should be applied first and required for Korean society in the view of society system (regime) and a point of view for minimizing side effect as UAS popularization.